Heurística da ancoragem e ajustamento em estimativas numéricas de bens de consumo: uma aplicação considerando a estratificação socioeconômica dos agentes no município de Fortaleza - CE - Pereira, Ohanna Larissa Fraga (2018)
Studies of the decision-making behavior of individuals in the Economis are progressively diverging from the reductionist view of the mainstream conception of the homo economicus. In this context, Behavioral Economics advances as an alternative to this approach, assuming that the limited rationality of agents leads them to simplifying rules in decision making, called heuristics. Tversky and Kahneman mapped three main heuristics, one of which is the anchoring and adjustment heuristic, which occurs when the final estimate of the agent is based on a put anchor, which is still insufficiently adjusted to produce a final biased response. The main objective of this work is to analyze the effects of this heuristic on numerical estimates of consumption items of the general population investigated and among the Low, Medium and High socioeconomic Strata of the individuals from Fortaleza. For that, an empirical research was carried out through the application of questionnaires with agents belonging to the three socioeconomic strata cited, with subsequent analysis according to the statistical procedures proposed by Jacowitz and Kahneman. The results indicated a great influence of the anchoring effect on the decisions of the Fortaleza’s agents, especially of the low anchors. The Lower Stratum was more influenced by the anchors than the Middle, which, in turn, suffered greater influence than the High. The items common to the consumption basket of all strata had lower Anchoring Indices, while goods and services with higher consumption inequalities showed higher indices in the Lower Stratum, intermediate in the Middle Stratum and lower in the High Stratum. In addition, it was possible to identify that the agents confidence in their estimations has a direct relation with the anchoring effect, so that the individuals more uncertain about their estimates suffered a greater effect of the anchors, while the more confident ones obtained visibly lower anchoring indices, although significant. Thus, the data revealed that the socioeconomic stratification is capable of affecting the numerical estimates of the individuals through the anchoring heuristic and adjustment in the consumption environment.